Copper-catalyzed oxidative coupling reaction of α, β-unsaturated aldehydes with amidines: synthesis of 1, 2, 4-trisubstituted-1H-imidazole-5-carbaldehydes. Issue 12 (13th November 2015) - Li, Yaxuan; Fu, Yajie; Ren, Chaojie; Tang, Dong; Wu, Ping; Meng, Xu; Chen, Baohua
Abstract : A convenient synthesis of 1, 2, 4-trisubstituted-1 H -imidazole-5-carbaldehydes was developed, which features high atom economy, cheap catalysts and mild conditions. Abstract : A practical and highly functional group-compatible synthesis of 1, 2, 4-trisubstituted-1 H -imidazole-5-carbaldehydes has been developed via copper-catalyzed oxidative coupling of amidines and α, β-unsaturated aldehydes, which features aldehyde preservation, cheap catalysts, as well as high atom economy and mild conditions.